Nonlocal Lagrange multipliers and transport densities - Azevedo, Assis (2023)
We prove the existence of generalised solutions of the Monge-Kantorovich equations with fractional $s$-gradient constraint, $0<s<1$, associated to a general, possibly degenerate, linear fractional operator of the type, \begin{equation*} \mathscr L^su=-D^s·(AD^su+\bs bu)+\bs d· D^su+cu , \end{equation*} with integrable data, in the space $Λ^{s,p}_0(Ω)$, which is the completion of the set of smooth functions with compact support in a bounded domain $Ω$ for the $L^p$-norm of the distributional Riesz fractional gradient $D^s$ in $\R^d$ (when $s=1$, $D^1=D$ is the classical gradient). The transport densities arise as generalised Lagrange multipliers in the dual space of $L^∞(\R^d)$ and are associated to the variational inequalities of the corresponding transport potentials under the constraint $|D^su|≤ g$. Their existence is shown by approximating the variational inequality through a penalisation of the constraint and nonlinear regularisation of the linear operator $\mathscr L^su$. For this purpose, we also develop some relevant properties of the spaces $Λ^{s,p}_0(Ω)$, including the limit case $p=∞$ and the continuous embeddings $Λ^{s,q}_0(Ω)\subset Λ^{s,p}_0(Ω)$, for $1\le p\le q\le∞$. We also show the localisation of the nonlocal problems ($0<s<1$), to the local limit problem with classical gradient constraint when $s→1$, for which most results are also new for a general, possibly degenerate, partial differential operator $\mathscr L^1u$ only with integrable coefficients and bounded gradient constraint.